Conjugated Polymers: Reversible Electronic Solid–Gel Switching of a Conjugated Polymer (Adv. Sci. 2/2020). Issue 2 (22nd January 2020) - Gladisch, Johannes; Stavrinidou, Eleni; Ghosh, Sarbani; Giovannitti, Alexander; Moser, Maximilian; Zozoulenko, Igor; McCulloch, Iain; Berggren, Magnus
Abstract : In article number 1901144, Eleni Stavrinidou, Magnus Berggren, and co‐workers present a conjugated polymer that exhibits unprecedented volume change when electrochemically addressed. The thiophene‐based polymer expands between 1000% and 10 000% irreversibly and 300% reversibly when oxidized. Molecular Dynamics reveal that the polymer transforms between a solid state to gelled state upon redox switching.